Aturan Utang dalam Akad Pembiayaan Mudharabah pada Bank Syariah - Yusriadi, Yusriadi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
Mudharabah financing is financing in the form of cooperation between two or more Islamic banks, in which the owner of the capital entrusts a certain amount of capital to the manager with a profit sharing agreement, or in another language as shahibul maal which provides all the capital and the customer as mudharib who manages the funds. The profits obtained by the business are in accordance with the initial agreement as stated in the contract. However, if there is a loss, it will be borne by the Islamic bank if the loss is not due to the intention of the insurer's customer, while the customer loses time, energy and thought. If the loss is caused by the negligence of the customer, the customer must bear the loss himself. However, the mudharabah financing at one of the Islamic banks has not shown the character of the mudharabah financing completely and correctly because the concept of debt appears in the contract.